OpinionSeer: Text visualization on hotel customer reviews of services and physical environment - Lee, Angela Siew Hoong *; Chong, Daniel Ka Leong *; Chan, Khin Whai (2018)
The popularity of online platforms such as social media, review websites and blogs in recent years has increased the volume of user-generated content. Travel websites such as TripAdvisor, Agoda, Booking.com has been a popular companion to many travellers when deciding which hotels to stay and where to go in a foreign country. Travel websites such as TripAdvisor, Agoda and Booking.com are sources for consumers to obtain past experiences, reviews and recommendations from other travellers who have visited a specific hotel. Thus, organizations and businesses now turn to big data analytics to inspire them to discover hidden insights and gain better understanding. In this paper, we study several factors which are impacting customer satisfaction and to identify various hidden insights towards travellers’ experience through text mining.